2016
DOI: 10.4103/0019-5413.193477
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous vertebroplasty guided by preoperative computed tomography measurements

Abstract: Background:Percutaneous vertebroplasty (PVP) is now widely performed to treat painful vertebral compression fractures. Previous researches have reported numerous advantages. However, it rarely reported that how to determine the feasibility of the unilateral or bilateral approach and how to decide the puncture angle, the skin insertion site before the procedure. The aim of this study was to discuss the feasibility of PVP using unilateral pedicular approach by the three-dimensional positioning of computed tomogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…PVP assisted by preoperative computed tomography (CT) digital design is increasing recently. Some researchers have reported that an improved PVP performed with preoperative CT design can boost the success rate of pedicle puncture, 12 but weak clinical practicability limits its further more application. Currently, a kind of economic, simple, and accurate technique for percutaneous puncture is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…PVP assisted by preoperative computed tomography (CT) digital design is increasing recently. Some researchers have reported that an improved PVP performed with preoperative CT design can boost the success rate of pedicle puncture, 12 but weak clinical practicability limits its further more application. Currently, a kind of economic, simple, and accurate technique for percutaneous puncture is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…But it is necessary to repeat the operation twice in bilateral transpedicular puncture, use two sets of operating instruments, and increase operation time and radiation exposure time, which also increase patients’ economic burden. Therefore, more and more scholars tend to use unilateral transpedicular puncture approach 9–11 . However, in clinical use of unilateral transpedicular percutaneous kyphoplasty for the treatment of osteoporotic vertebral compression fractures, we found that some patients had no significant relief of postoperative pain symptoms or still had residual partial pain.…”
Section: Introductionmentioning
confidence: 99%